Processo AQUA de certificação de edificações sustentáveis na fase operação e uso: estudo de caso do escritório verde da UTFPR - Lima, Lucimara Ferreira de (2013)
Environmental imbalances resulting from the lack of compatibility between the population growth and the exhaustibility of natural resources bring out great challenges. In such a context, the industry of civil engineering must be pointed out, for the use of great quantities of non-renewable resources in its production chain. The current production practices used in civil construction need immediate adjustments so that the sector may contribute appropriately for the sustainable development of the country. Unfortunately, it is still rather common to find artisanal processes on work fronts, use of raw materials without sustainable handling and the application of industrialized products with disregard to aspects such as water conservation, energy and the necessary reduction of residues and waste. The appearance of assessment and certification systems of civil construction in different parts of the world has reduced the negative impacts caused by the construction sector. Over the last years, such movement has gained new supporters and numbers have become more expressive, pointing towards a pressing demand for new actions by professionals and corporations in the field. The study performed consists of analyzing the AQUA´s Technical Report of Operation and Use, designed by the Vanzolini Foundation in 2010 as a temporary version, which is currently being revised. Such analysis has been used as the basis for the undertaking of a case study on the construction of the Green Office at UTFPR. The outcome of such research is the assessment of the office´s environmental performance as for conformity with requirements defined on the AQUA standard of buildings operation, as well as the treatment of non-conformities and undertaking of corrective and preventive actions in order to achieve satisfactory performance. Thus, such thesis is the summary of a certification process of sustainable buildings and aims to emphasize the importance of certification in civil construction as a way of assuring that buildings are planned, designed, built and primarily used according to the principles of sustainability: technical, economic, social, environmental, and cultural aspects, which must interact holistically.